Fetal extraction in intact amniotic sac in twins - N R Akhmadeyev; I F Fatkullin (RUDN Journal of Medicine, 2012)
The results of operations of cesarean section in twin gestations with the extraction of fetuses in the intact amniotic sac and the condition of newborns were analyzed. Main (experimental) and control study groups of abdominally delivered twin pregnant have been formed, and also two groups of the children delivered by these operations. Analysis of efficacy of the extraction in the intact amniotic sac method on the newborns’ showed that the Apgar score in the experimental group was higher, artificial lung ventilation duration, duration of hospital stay was less, and prevalence and severity of neurological disorders was less. Duration of operations increased by less than 5%. Hence condition of multifetal newborns improvement expected while using this method.